Diverse clinical manifestations of acquired vulvar lymphangioma: a report of five cases in Vietnamese women - Tho Thi Thanh Nguyen; Anh Nguyen Ngoc Hoang; Thu Nguyen Anh Luu; Thuy Thi Phan Nguyen; Em Van Loi Doan; Tu Nguyen Anh Chan; Hao Trong Nguyen (PAGEPress Publications, 2024)
Acquired vulvar lymphangioma (AVL) is a rare but important condition that requires prompt diagnosis and appropriate management to alleviate symptoms and prevent complications. AVL can erupt locally as isolated or clustered lesions which range from translucent, fluid-filled vesicles to smooth, flesh-colored papules or nodules that exude serous or crystalline liquid spontaneously or after trauma. Clinically, it can also be asymptomatic. However, symptoms are commonly accompanied by vulvar itching, burning, soreness, or unpleasant discharge. Here, we report a case series of five Vietnamese patients with AVL with diverse clinical features.